Association between access to dental services and altitude of the residence of Peruvian children - Nicolle Ventocilla-Vargas; Vanessa Salinas-Zevallos; Kelly Vásquez-Julca; Roberto Antonio León-Manco (Editorial Ciencias Médicas, 2023)
Introduction: Access to dental services is important to guarantee adequate oral health. Therefore, it is important to assess the geographical barriers that may affect access, such as altitude. Objective: To determine the association between access to dental services and the altitude of residence of children under 12 years of age in Peru, 2019. Methods: The study was a cross-sectional with a sample of 42,350 records of children under 12 years of age. The variables were access to dental care, time of dental care, place of dental care, altitude, region, area of residence, place of residence, natural region, health insurance, wealth index, sex and age. A descriptive and bivariate analysis was performed with the chi square test. The results underwent multivariate analysis using Poisson regression to obtain prevalence ratios and adjusted prevalence ratios. There was a confidence level of 95% and p < 0.05. Results: It was found that altitude was linked to access to dental care (PR = 1.15; 95% CI: 1.12 - 1.18; p < 0.001), it was also found when considering the variables area of residence, place of residence, natural region, health insurance, wealth index, sex and age (RPa = 1.10; 95% CI: ºº1.04 - 1.16; p < 0.001). Conclusions: In 2019, Peruvian children under 12 years, living at more than 2500 masl, were more likely to receive dental care in the last 2 years.